Tuning localized surface plasmon resonance of star-like gold nanoparticles by in situ growth on crystalline nanocellulose for SERS substrates - Alfredo Ayala-Fonseca; Gonzalo Ramírez-García; Andrés De Luna Bugallo; Elder De la Rosa; Pedro Salas (JPhys Photonics, 2025)
The influence of crystalline nanocellulose (CNC) played a crucial role in modulating the local surface plasmon resonance (LSPR) of star-like gold nanoparticles (SAuNPs), acting as both a diffusion barrier and a chemical reducer during the growth of anisotropic nanoparticles (NPs). This effect was investigated using UV–Vis spectroscopy and transmission electron microscopy (TEM), leading to an enhanced analytical response in surface-enhanced Raman spectroscopy (SERS) substrates. The star-like AuNPs were synthesized via silver ion-guided anisotropic growth, using Turkevich gold NPs as seeds. As the CNC concentration increased, the LSPR of the NPs shifted from 520 nm to 835 nm, indicating an increase in Feret’s diameter. TEM analysis confirmed that higher CNC concentrations yielded larger NPs with more defined spikes, reflecting greater anisotropy. The SERS substrates were fabricated by depositing the hybrid material onto polytetrafluoroethylene membranes through vacuum filtration, making them suitable for integration into wearable devices. The potential of these NPs as SERS substrates was evaluated using 4-aminothiophenol (4-ATP) as a model molecule. The substrates exhibited high sensitivity, with the 0.3CNC0.08Au sample (CNC: 0.3 mg ml ^−1 , Au: 0.08 mg ml ^−1 ) detecting multiple vibrational modes of 4-ATP at a limit of detection of 1.048 × 10 ^−9 M. Furthermore, SERS intensity increased with CNC concentration up to a critical threshold, beyond which NP growth was inhibited. These findings demonstrate the ability to control the size, shape, and SERS activity of AuNPs by adjusting CNC concentration, offering valuable insights for designing efficient SERS substrates for analytical applications.